Ancestral Mutations Acquired in Refrex-1, a Restriction Factor against Feline Retroviruses, during its Cooption and Domestication - Ito, Jumpei; Baba, Takuya; Kawasaki, Junna; Nishigaki, Kazuo (Journal of virology, 2016)
Endogenous retroviruses (ERVs) are remnants of ancestral retroviral infections of germ cells. Retroviral endogenization is an adaptation process for the host genome, and ERVs are gradually attenuated or inactivated by mutation. However, some ERVs that have been “domesticated” by their hosts eventually gain physiological functions, such as placentation or viral resistance. We previously reported the discovery of Refrex-1, a soluble antiretroviral factor in domestic cats that specifically inhibits infection by feline leukemia virus subgroup D (FeLV-D), a chimeric virus of FeLV, and a feline ERV, ERV-DC. Refrex-1 is a truncated envelope protein (Env) encoded by both ERV-DC7 and ERV-DC16 proviral loci. Here, we reconstituted ancestral and functional Env from ERV-DC7 and ERV-DC16 envelope genes ( env ) by inducing reverse mutations. Unexpectedly, ERV-DC7 and ERV-DC16 full-length Env (ERV-DC7 fl and ERV-DC16 fl), reconstructed by removing stop codons, did not produce infectious viral particles. ERV-DC7 fl and ERV-DC16 fl were highly expressed in cells but were not cleaved into surface subunits (SU) and transmembrane subunits, nor were they incorporated into virions. G407R/N427I-A429T and Y431D substitutions within the SU C-terminal domain of ERV-DC7 fl and ERV-DC16 fl, respectively, caused these dysfunctions. The residues glycine 407 and tyrosine 431 are relatively conserved among infectious gammaretroviruses, and their substitution causes the same dysfunctions as the tested retroviruses. Our results reveal that specific mutations within the SU C-terminal domain suppressed Env cleavage and incorporation into virions and indicate that these mutations contributed to the domestication of Refrex-1 through multistep events that occurred in the postintegration period. IMPORTANCE Domestic cats are colonized with various exogenous retroviruses (exRVs), such as feline leukemia virus (FeLV), and their genomes contain numerous ERVs, some of which are replication-competent proviruses. The feline hosts, exRVs, and ERVs have complicated genetic interactions and provide an interesting field model for triangular relationships: recombination between FeLV and ERV-DC, which is a feline ERV, generated FeLV-D, a chimeric virus, and FeLV-D is restricted by Refrex-1, an antiretroviral factor corresponding to truncated Env of ERV-DC7 and ERV-DC16. Here, we reconstructed ancestral, functional Env from ERV-DC7 and ERV-DC16 env by inducing reverse mutations to elucidate how Refrex-1 was generated from its ancestor. Our results reveal that they were repeatedly inactivated by mutations preventing Env maturation. Our results provide insights into how ERVs were “domesticated” by their hosts and identify the mutations that mediated these evolutions. Notably, experiments that restore inactivated ERVs might uncover previously unrecognized features or properties of retroviruses.